Upregulation of Insulin and Ecdysone Signaling in Relation to Diapause Termination in Bombyx mori Eggs Exposed to 5 °C - Shi-Hong Gu; Pei-Ling Lin (Insects)
In the present study, we investigated the possible correlation between insulin/ecdysone signaling and chilling-induced egg diapause termination in Bombyx mori. Changes in insulin (bombyxin-Z1) and ecdysteroid-phosphate phosphatase (EPPase) gene expression levels in chilled eggs (whose diapause had been terminated by chilling to 5 °C for 90 days) exhibited no significant increase after being transferred to 25 °C, which differed from both non-diapause eggs and HCl-treated eggs. We further compared the differential temporal expressions of insulin (bombyxin-A6, -Y1, and -Z1), ecdysone signaling (EPPase and E75A), and metabolic-related (trehalose transporter 1 (Tret1) and trehalase 1 (Treh1)) as well as sorbitol dehydrogenase 2 (SDH2) genes between chilled eggs and eggs kept at 25 °C. Our results showed that all gene expressions remained at very low levels in eggs kept at 25 °C. However, in chilled eggs, differential temporal changes were detected according to different genes, with bombyxin-A6 and EPPase gene expression levels being maintained at relatively constant, high levels. Higher expression levels of the E75A, Tret1, and Treh1 genes were also detected in chilled eggs. Expressions of the SDH2 and bombyxin-Z1 genes decreased during the first 15 days and then increased between days 30 and 90 of chilling. Ecdysteroid levels and phosphorylation of glycogen synthase kinase (GSK)-3β, a downstream target of insulin signaling, were maintained at relatively higher levels in chilled eggs. These results suggested that due to relatively higher insulin and ecdysone signaling levels in chilled eggs, relatively higher glucose metabolism was sustained, leading to the continued depletion of metabolic reserves. On day 30 of chilling, as a means to adjust nutrient requirements and maintain embryonic nutrient homeostasis, SDH2 gene expression began to increase, followed by increased expression of the bombyxin-Z1 gene. Along with high expressions of the bombyxin-Z1 and SDH2 genes, a decreased sorbitol level was suggested to eventually terminate diapause in B. mori eggs. To our knowledge, this is the first study to demonstrate the correlation between insulin/ecdysone signaling and chilling-induced embryonic diapause termination.